Novel peptide-based materials assemble into adhesive structures: circular dichroism, infrared spectroscopy, and transmission elect[r]on microscopy studies - Warner, Matthew D. (Kansas State University, 2009)
Biologically based adhesives offer many industrial advantages over their chemically synthesized counterparts, not the least of which are reduced environmental impact and limited toxicity. They also represent a renewable resource. In addition, nanoscale biomaterials also show an incredibly large potential for biomedical uses, including possible drug delivery and novel wound bandaging, as well as tissue engineering. Understanding the adhesion mechanisms at work in peptide-based nanomaterials is key for producing viable industrial and clinical biomimetic compounds. Our previous work has shown that small hydrophobic oligopeptide segments flanked by short tri-lysine sequences display adhesion strength that is dependent on the formation of β-structure and large-scale association of monomers. In this study, three oligopeptides were synthesized based on putative amyloid fibril nucleation sites. Two of the sequences originate from the Alzheimer’s beta amyloid peptide Aβ1-40, while the third sequence comes from a nucleation site for islet amyloid polypeptide (IAPP). These peptides show unusual structural properties associated with adhesive ability. Furthermore, they represent a third category of requirements for β-structure formation. In addition, I report the first morphological evidence for the previously predicted structural mechanism underlying our previous peptide based adhesives.
Keywords: Beta amyloid; Nucleation sequence; Adhesive; Biologically-based materials; Fibril formation; Alzheimer's; Biology, Neuroscience (0317); Biophysics, General (0786); Chemistry, Biochemistry (0487)